(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the topic of linguistic interference and its impact on second language learning. The main focus is on the interaction between the native language and the language being studied, and the consequences of this process for language acquisition. The theoretical and practical aspects of studying interference phenomena in linguistics are discussed, attempting to explain how these processes occur during the interaction of two languages and how this interaction can affect the effectiveness of language learning. The article also distinguishes between the negative and positive aspects of interference and proposes methods to reduce or prevent it during language learning. The problem of interference arises due to the presence in the learners’ minds of the linguistic rules of the native language, which can cause various difficulties in the learning process. It also delineates the concepts of language contact, bilingualism, and interference, and analyzes the role of each in the language learning process.